A relação afetiva com a leitura: memórias de professores - Ferreira, Eliane Aparecida Galvão Ribeiro [UNESP]; Valente, Thiago Alves (My University, 2012)
In the area of humanities, especially in Literature, can cause estrangement that perform research related to the creation of the database. It can imagine at first that tries to bring complex concepts such as "literature", "reading" and "literacy" to quantifications. However, it should be noted that the formation of these banks can contribute to the consolidation of research networks, with consequent exchange of information and references, including researchers from different and distant regions of country. Precisely because of this diverse spatiality, providing that the Federation units realize their research capacities and performance in certain areas brings significant elements for the advancement of scientific and cultural. In the case of this research aimed to briefly describe some clues about memories of reading teachers in the Literature, the region known as Norte Pioneiro, of Paraná State and the neighboring region with that, demarcated by the counties between Assis and Ourinhos from São Paulo State, enrolled in a specialized course, to contemplate works of juvenile literature.

Na área de Humanidades, sobretudo em Letras, pode causar estranhamento que se realize pesquisa voltada à constituição de banco de dados. Pode-se imaginar, a princípio, que se tenta submeter conceitos complexos como “literatura”, “leitura” e “letramento” a quantificações. Contudo, é preciso notar que a formação desses bancos pode contribuir para a consolidação de redes de pesquisa, com consequente troca de informações e referências, entre pesquisadores das mais diversas e distantes regiões do país. Justamente devido a essa espacialidade diversa, propiciar que as unidades da Federação percebam suas condições de pesquisa e desempenho em determinadas áreas traz elementos significativos para o avanço dos trabalhos científicos e culturais. No caso desta pesquisa, objetivou-se expor sucintamente alguns indícios sobre memórias de leitura de professores da área de Letras, da região conhecida como Norte Pioneiro, do Estado do Paraná e da região limítrofe com aquela, demarcada pelos municípios paulistas de Assis e Ourinhos, no Estado de São Paulo, inscritos em um curso de especialização, que contemplassem obras de literatura juvenil.
Keywords: Literature; Affective memory; Expertise; Paraná; São Paulo; Memórias de leitura; Literatura e ensino; Formação do leitor